Dream of a Poetry of Defense: The Double Lyrics of Timothy Donnelly - Lee Spinks (European Journal of American Studies)
This article presents the first extended critical engagement with the work of the contemporary American poet Timothy Donnelly. It suggests that central to Donnelly’s practice is his crafting of a style of double lyric to explore the simultaneous forming and fragmentation of the modern American public sphere across the reciprocating realms of politics, economics, culture and information technology. In examining this double writing the article also considers Donnelly’s cultivation of a poetics of the “many” or multitude to imagine a democratic alternative to the political economy of late neoliberalism and neoliberal imperialism.